Eucheuma cottonii seaweed-based biochar for adsorption of methylene blue dye - Saeed, A.A.H. (MDPI, 2020)
Pollution from dye containing wastewater leads to a variety of environmental problems, which can destroy plant life and eco-systems. This study reports development of a seaweed-based biochar as an adsorbent material for efficient adsorption of methylene blue (MB) dye from synthetic wastewater. The Eucheuma cottonii seaweed biochar was developed through pyrolysis using a tube furnace with N2 gas, and the properties were later improved by sulfuric acid treatment. The adsorption studies were conducted in a batch experimental setup under initial methylene blue concentrations of 50 to 200 mg/L, solution pH of 2 to 10, and temperature of 25 to 75â¦C. The characterization results show that the developed biochar had a mesoporous pore morphology. The adsorbent possessed the surface area, pore size, and pore volume of 640 m2/g, 2.32 nm, and 0.54 cm3/g, respectively. An adsorption test for 200 mg/L of initial methylene blue at pH 4 showed the best performance. The adsorption data of the seaweed-based biochar followed the Langmuir isotherm adsorption model and the pseudo-second-order kinetic model, with the corresponding R2 of 0.994 and 0.995. The maximum adsorption capacity of methylene blue using the developed seaweed-based biochar was 133.33 mg/g. The adsorption followed the chemisorption mechanism, which occurred via the formation of a monolayer of methylene blue dye on the seaweed-based biochar surface. The adsorption performance of the produced seaweed biochar is comparable to that of other commercial adsorbents, suggesting its potential for large-scale applications. Â© 2020 by the authors. Licensee MDPI, Basel, Switzerland.